Legal Economic Politics in Eradicating Criminal Acts of Corruption in State-Owned Enterprises - Firmansyah, Amir; Suparji, Suparji; Adji, Indriyanto Seno (Jurnal Cita Hukum, 2024)
This paper analyses the function of State-Owned Enterprises (SOEs) in bolstering the national economy and the substantial obstacles they encounter in addressing corporate corruption.  State-owned enterprises serve a crucial role as primary agents of national development, especially in infrastructure, energy, and strategic sectors. Their dual role—catering to public and commercial interests—frequently subjects them to governance challenges and corruption vulnerabilities.  This research seeks to elucidate the operational dynamics of state-owned enterprises (SOEs) as primary stewards of the national economy, while concurrently examining their involvement in mitigating corporate criminal activities.  The study examines the utilisation of the business judgment rule to protect SOE directors from legal accountability concerning sound faith business judgments and the overarching legal-political backdrop influencing anti-corruption initiatives.  The study utilises a qualitative research method, incorporating a literature analysis and a legislative approach.  It examines diverse statutory rules and legal principles and records instances of corruption related to state-owned enterprises, utilising scholarly articles from the law, governance, and economics disciplines.  The findings indicate that while the business judgment rule offers essential protection for corporate decision-makers, inadequate internal controls, political meddling, and unclear legal obligations persist in obstructing efficient governance within state-owned enterprises (SOEs).  Moreover, the inconsistent implementation of anti-corruption policies diminishes their efficacy.  The report indicates that extensive reform is necessary to enhance legal responsibility, increase transparency, and professionalise the administration of state-owned enterprises.  Enhancing institutional control and maintaining regulatory compliance are essential measures to protect the strategic role of state-owned enterprises in fostering sustainable and corruption-free economic development.